The Sociality and Liminality of Bangkok’s Cannabis Cafés - Fong, Jack (Qualitative Sociology Review, 2025)
In June 2022, Thailand became the first country in Asia to decriminalize cannabis, only to face opposition from conservative political forces that are now attempting to pass policies that will recriminalize its recreational use. My qualitative study conducted between summer 2022 and the conclusion of 2024 examines the sociality of 45 cannabis cafés in the capital Bangkok despite these developments, enhanced by my status as having grown up in the city and speaking the Thai language and local Chinese dialects. Employing urban sociological concepts such as Ray Oldenburg’s third places and Lyn Lofland’s notion of the urban experience as characterized by interactions with strangers, I describe Bangkok’s cannabis cafés as third places that reduce the status of the stranger, and thus destress the actor in its lifeworld. These dynamics are argued to counter Bangkok’s over-stimuli and stressor-filled experiences, now challenged by policy developments that place the continuing operations of cannabis cafés in a liminal state.